Reprint of "Nuclear transport factors: global regulation of mitosis". (June 2015) - Forbes, Douglass J; Travesa, Anna; Nord, Matthew S; Bernis, Cyril
Abstract : The unexpected repurposing of nuclear transport proteins from their function in interphase to an equally vital and very different set of functions in mitosis was very surprising. The multi-talented cast when first revealed included the import receptors, importin alpha and beta, the small regulatory GTPase RanGTP, and a subset of nuclear pore proteins. In this review, we report that recent years have revealed new discoveries in each area of this expanding story in vertebrates: (a) The cast of nuclear import receptors playing a role in mitotic spindle regulation has expanded: both transportin, a nuclear import receptor, and Crm1/Xpo1, an export receptor, are involved in different aspects of spindle assembly. Importin beta and transportin also regulate nuclear envelope and pore assembly. (b) The role of nucleoporins has grown to include recruiting the key microtubule nucleator – the γ-TuRC complex – and the exportin Crm1 to the mitotic kinetochores of humans. Together they nucleate microtubule formation from the kinetochores toward the centrosomes. (c) New research finds that the original importin beta/RanGTP team have been further co-opted by evolution to help regulate other cellular and organismal activities, ranging from the actual positioning of the spindle within the cell perimeter, to regulation of a newly discovered spindle microtubule branching activity, to regulation of the interaction of microtubule structures with specific actin structures. (d) Lastly, because of the multitudinous roles of karyopherins throughout the cell cycle, a recent large push toward testing their potential as chemotherapeutic targets has begun to yield burgeoning progress in the clinic.